Genomic Alterations in Melanocytic Tumors: A Review of Spitz Tumors, Blue Nevi, Deep Penetrating Melanocytomas and Pigmented Epithelioid Melanocytomas - Rayan Saade; Rami N. Al-Rohil (Applied Sciences, 2024)
The arena of melanocytic histopathology has experienced tremendous growth in the last decade. The advancement is attributed to incorporating various molecular tests in benign, intermediate, and malignant melanocytic tumors. Most molecular testing has been mainly applied in clinically advanced-stage melanoma to determine the molecular alteration to help guide therapy (e.g., BRAF inhibitors in BRAF mutated melanomas). However, with more availability and, to a certain degree, affordability of certain molecular tests, multiple studies have been conducted on benign/intermediate lesions in an attempt to understand further the driving molecular alterations allowing for the proliferation of certain melanocytic lineages. This review article discusses and illustrates examples of recently recognized entities with their corresponding genomic alterations in the Spitz lineage, blue nevi, deep penetrating melanocytomas, and pigmented epithelioid melanocytomas.